Evolving IT governance practices for IT and business alignment: A case study in an Australian institution - Bhattacharjya, Jyotirmoyee; Chang, Vanessa (The Information Institute, 2006)
Over the past decade, IS/IT governance has become a key issue of concern for senior IT decision makers around the world. The underlying goals for adopting formal IT governance practices are improvement of business performance and conformance with regulations. This exploratory study examines how IT governance is implemented in an Australian organization through a number of IT governance structures, processes, and relational mechanisms. The study reveals a number of important findings in the context of the implementation of IT governance in a higher education environment. The relationship between IT governance implementation and IT-business alignment issues will also be discussed further in the paper.